Women’s Fertility and their Education: Evidence from Indonesia - Yameogo, Audrey (Université d'Ottawa | University of Ottawa, 2017)
The contribution of education can extend beyond the individuals economic returns and influence their behavior when it comes to making personal decisions. The present study exploits the intensity of the Sekolah Dasar INPRES program in Indonesia to evaluate the effects of education on fertility and family decisions of women of Java island. Adopting a difference-in-differences approach, I compare co- horts of women that were potentially affected by the program to unaffected cohorts. I find evidence that girls who benefited from the program decreased their use of contraception by 4.6 percentage points at their maturity. The variables corresponding to their number of children before they reach 21, their age of first marriage, first intercourse and first birth remain unchanged and these results are robust to different specifications.